A study on the mnemotropic and antidepressant-like effects of the low-molecular-weight mimetic of nerve growth factor, dipeptide GK-2, in experimental ischemic stroke - P. Yu. Povarnina; N. M. Sazonova; D. M. Nikiforov; T. A. Gudasheva; V. L. Dorofeev (Фармакокинетика и Фармакодинамика)
Relevance. The nerve growth factor (NGF), possessing neuroprotective and neuroregenerative properties, holds promise for the development of medications for the treatment of post-stroke conditions. At the Federal Research Center for Innovator and Emerging Biomedical and Pharmaceutical Technologies, a dimeric dipeptide mimic of NGF with the laboratory code GK-2 was designed and synthesized. Under conditions of experimental cerebral ischemia, it significantly reduced the volume of brain infarction and stimulated neuro- and synaptogenesis.Objective. The aim of this study was to investigate the effects of GK-2 on experimental post-stroke dementia and depression.Methods. Ischemic stroke was induced by occlusion of the middle cerebral artery (MCAO) in Wistar rats. GK-2 was administered intraperitoneally at a dose of 0.5 mg/kg for 21 days post MCAO. Short-term and long-term memory of the animals were assessed 30–40 days post MCAO using the novel object recognition test. Depressive-like state was evaluated through the forced swimming test and sucrose preference test.Results. In animals subjected to MCAO, both short-term and long-term memory exhibited a statistically significant decline of 80 %, along with a depressive-like state characterized by a 50 % increase in total immobility time and a 30 % reduction in sucrose preference, when compared to the sham-lesioned group. Dipeptide GK-2 completely averted the onset of these impairments.Conclusion. The dipeptide mimic of NGF, GK-2, mitigates the development of cognitive and psychomotional impairments in the setting of experimental stroke.